2008
DOI: 10.1186/cc6973
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sleep disturbances and long-term reduced health-related quality of life after critical care: a prospective multicenter cohort study

Abstract: IntroductionThe aim of the present prospective multicenter cohort study was to examine the prevalence of sleep disturbance and its relation to the patient's reported health-related quality of life after intensive care. We also assessed the possible underlying causes of sleep disturbance, including factors related to the critical illness.MethodsBetween August 2000 and November 2003 we included 1,625 consecutive patients older than 17 years of age admitted for more than 24 hours to combined medical and surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
3
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 34 publications
3
80
3
10
Order By: Relevance
“…This is in line what we have previously presented for ICU patients. (13)(14)(15) but is contrary to the findings of Ringdal et al who found a correlation between longer stay in ICU and worse physical function and limitations of roles as a result of physical problems. (26,30) This outcome may be due to a shorter follow-up period in that study 26 .…”
Section: Effects Of Trauma and Icu Related Factorscontrasting
confidence: 71%
See 1 more Smart Citation
“…This is in line what we have previously presented for ICU patients. (13)(14)(15) but is contrary to the findings of Ringdal et al who found a correlation between longer stay in ICU and worse physical function and limitations of roles as a result of physical problems. (26,30) This outcome may be due to a shorter follow-up period in that study 26 .…”
Section: Effects Of Trauma and Icu Related Factorscontrasting
confidence: 71%
“…(8) In three recent studies we have found that pre-existing disease is a major contributor to a reduced HRQoL after critical care for reasons other than trauma. (13)(14)(15) However, pre-existing disease is thought to be less prevalent in this group of patients and is therefore seldom investigated in injured patients. The overall aim of the study was to assess pre-existing diseases, their rate and 4 distribution and to examine their possible long term (2 years) effects on HRQoL in a group of patients with trauma injuries who required intensive care.…”
Section: Introductionmentioning
confidence: 99%
“…The cohort used in this study is a part of a large study that has previously been examined from several different perspectives [6,18,26] . Health related quality of life has been examined short and long term.…”
Section: Discussionmentioning
confidence: 99%
“…The instrument is internationally well known and has often been used [25]. SF-36 has previously been applied in intensive care [6,[26][27][28], and has recently been recommended as one of the best-suited instrument for measuring HRQoL in trials in critical care [29].…”
Section: Health Related Quality Of Lifementioning
confidence: 99%
“…Providing caring actions aimed at preventing the development of such negative memories and experiences is complex since it is the medical condition as such, drugs and not least the caring environment itself that influence memories from ICU care. Studies concerning health-related quality of life and patients show that it takes a long or a very long time to return to life as it was before the ICU stay (Orwelius et al, 2008;Ringdal et al, 2009Ringdal et al, , 2010Samuelson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%